Nonlinear bending and stability of ellipsoidal shell interacting with liquid - Ganeeva, Muzaina Saitgareevna; Moiseeva, Valeria Evgenievna; Skvortsova, Zara Vladimirovna (Computational Continuum Mechanics, 2011)
This paper studies the axisymmetric bending and stability of an oblate ellipsoidal shell under liquid pressure on the convex side of the shell, and in the case when the shell comes into contact with an incompressible liquid. Nonlinear geometrical and physical relations of the theory of shells are applied. The liquid pressure varies according to the adiabatic law. The results indicate that the nonlinear deformation depends on the characteristics of the loading medium. It is shown that the variability of the curvature of the middle surface is responsible for the peculiarities of the stress-strain state of the shell under consideration.
Keywords: bending; stability; ellipsoidal shell; liquid; interaction